2011
DOI: 10.1111/j.1752-1688.2011.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Source and Delivery of Nutrients to Receiving Waters in the Northeastern and Mid-Atlantic Regions of the United States1

Abstract: This study investigates nutrient sources and transport to receiving waters, in order to provide spatially detailed information to aid water-resources managers concerned with eutrophication and nutrient management strategies. SPAtially Referenced Regressions On Watershed attributes (SPARROW) nutrient models were developed for the Northeastern and Mid-Atlantic (NE US) regions of the United States to represent source conditions for the year 2002. The model developed to examine the source and delivery of nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 45 publications
4
75
0
Order By: Relevance
“…450.12 kg/km 2 /year, respectively, as shown in Table ). These coefficients are comparable to results from other SPARROW models (Moore et al ., ; Rebich et al ., ; Wise and Johnson, ).…”
Section: Resultsmentioning
confidence: 98%
“…450.12 kg/km 2 /year, respectively, as shown in Table ). These coefficients are comparable to results from other SPARROW models (Moore et al ., ; Rebich et al ., ; Wise and Johnson, ).…”
Section: Resultsmentioning
confidence: 98%
“…It was found that the model coefficients performed well at explaining observed variation in the 2001 flux dataset; the r 2 value was 0.90 (Figure ). We also looked at past SPARROW studies and found that our baseline model resulted in calibrated parameters that are similar to those reported in other studies (Smith et al ., ; Alexander et al ., ; Hoos and McMahon, ; Najjar et al ., ; Brown et al ., ; Moore et al ., ; Rebich et al ., ; Robertson and Saad, ; Wise and Johnson, ; Alam and Goodall, ). Based on these past studies, we found a consistent negative relationship between N loading and mean annual T and a positive relationship between N loading and mean annual P .…”
Section: Resultsmentioning
confidence: 99%
“…Regional models, however, indicate that these processes typically result in a net loss of nitrogen in streams (Alexander et al. , 2007; Moore et al. , 2011) of generally <20%, attributable primarily to the loss of nitrate through benthic denitrification (Howarth et al.…”
Section: Methodsmentioning
confidence: 99%